S-MART BUSINESS PLAN (WARUNG â POS â RESTOCK) FINAL PROJECT - Wijaya, Michael
Indonesia is a currently uprising country with powerful economic potential. Abaft the tremendous success of Indonesia’s GDP in the past 5 years, lies several sectors that delivered the most prominent donation to the national GDP (in descending order): Trade, hotels and restaurants; manufacturing; and transportation and communication (Ndiame et al., 2018). However, the largest stable growth had been dominated by commodity-related and retail sector under the trade, hotels and restaurants segment’. Compared to the last 18 years, the number of jobs created by the agriculture segment had lowered more four multipliers whilst wholesale and retail trade had doubled to more than one million new job creation in the year 2015 to 2017, signaling a new trend of retail and manufacturing in Indonesian industry and overtaking the agriculture era. However, there is a concerning absence in terms of traceability in trade sector. The author sees a huge opportunity that lies in this uprising sector and has created an attentive business plan and conducted market analysis using quantitative method on 152 warung sample with 95% confidence interval in Bandung to enter Indonesia’s traditional grocery retail information industry. The result of this research suggest that the business plan holds huge risk and huge potential and will prevail if executed by the right people and funded by the right investor. , S-MART will disrupt and revolutionize Indonesia’s whole supply chain ecosystem, bringing digitalization to mom and dad shop across Indonesia, record and account all goods transaction that revolves in Indonesia, create insights faster and more reliable than any existing data and information company in Indonesia, and establish the largest retail store Indonesia in terms of volume and number of channels that will be little even Indomaret and Alfamart.